Solve for y t=6py

Math
t=6py
Rewrite the equation as 6py=t.
6py=t
Divide each term by 6p and simplify.
Tap for more steps…
Divide each term in 6py=t by 6p.
6py6p=t6p
Simplify 6py6p.
Tap for more steps…
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6py6p=t6p
Rewrite the expression.
pyp=t6p
pyp=t6p
Cancel the common factor of p.
Tap for more steps…
Cancel the common factor.
pyp=t6p
Divide y by 1.
y=t6p
y=t6p
y=t6p
y=t6p
Solve for y t=6py

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top